Valuing IKS in successive South African Physical Sciences Curricula. Issue 1 (2nd January 2016) - Taylor, Dale L.; Cameron, Ann
Abstract : The valuing of Indigenous Knowledge Systems (IKS) is one of the principles on which the South African school curriculum is supposed to be based. The purpose of this paper is to critique the treatment of indigenous knowledge in the South African secondary Physical Sciences curriculum against a backdrop of international debates on the relationship between IKS and science. Such debates usually take either an Inclusive perspective, where IKS are regarded as part of science, or an Exclusive perspective, where IKS and science are regarded as separate domains of knowledge. We identify a third perspective where IKS and science are viewed as intersecting domains. A document analysis of all national post-apartheid curriculum documents relevant to secondary Physical Sciences identifies only nine examples of IKS related to Physical Sciences in the latest curriculum documents (CAPS), although this is an improvement on the previous curricula. The curriculum documents reflect some confusion about the relationship between IKS and science, both in the wording and in the positioning of examples in relation to science content. Physical sciences curriculum development in South Africa appears to have gone through the stages of colonisation, decolonisation and neo-colonisation. We recommend the development of theory that addresses the role of valuing IKS in science classrooms. The Intersecting perspective offers promise as an approach to use in science classrooms, allowing the distinction to be made between pieces of indigenous knowledge that intersect with modern science knowledge and IKS as whole systems of thinking with distinctive worldviews.